Evaluating Nigeria’s National Development Plans: Addressing Contemporary Challenges and Seizing Strategic Opportunities - Abasilim, Ugochukwu David; Adelusi, Oluwatimileyin; Mudau, Thizwilondi J. (Universitas Medan Area, 2025)
This study evaluates Nigeria's National Development Plans (NDPs) from historical and contemporary perspectives to identify challenges and strategic opportunities to enhance their effectiveness in achieving sustainable development goals. The research employs a comprehensive literature review and analysis of the implementation of Nigeria's NDPs. This approach assesses the socio-economic impact and institutional constraints that have influenced the effectiveness of these development plans. The study finds that Nigeria's NDPs have consistently faced several challenges, including corruption, weak institutional capacity, political instability, limited private sector involvement, and insufficient inclusivity. These factors have significantly impeded the effectiveness of the plans and their contribution to sustainable development objectives. To improve the implementation and impact of Nigeria's NDPs, the study recommends strengthening anti-corruption measures, enhancing institutional capacity, promoting policy continuity, increasing private sector participation, and improving inclusivity in the planning processes. Addressing these areas can lead to more effective development planning and achieving sustainable development goals.